FENOMENA MUSIK METAL SEBAGAI SEBUAH IDENTITAS ANAK MUDA DI ARAB SAUDI PADA ERA GLOBALISASI ( Tinjauan Kepustakaan ) - Rifki Nur Rahmat (CMES (Center of Middle Eastern Studies), 2014)
The aims of this research are: (1) To describe the phenomenon of metalmusic in Saudi Arabia in the range of 1995-2010. (2) To explain the factors ofmetal music infiltration to Saudi Arabia. (3) To explain the identity of performermetal music in Saudi Arabia. Kind of research used in this thesis is qualitative research with descriptivemethod. Descriptive method is a method in researching the status of a group orpeople, an object, a certain condition, a system of thought, or an event in thepresent. Data collection technique used is literature research. Data analysis in thisstudy is using a qualitative analysis that includes: data collection, data reduction(summary) the data, data presentation and conclusion. This research resulted in several conclusions (1) The phenomenon of metalmusic in Saudi Arabia is the globalization process of metal music in the world,especially in the Middle East countries. Metal music is a genre of modern musicwhich has been evolving around the 1990s in the area of Saudi Arabia. (2) Ingeneral, there are two factors that brought metal music into the country of SaudiArabia, namely internal and external ones. The internal factor is the growth ofyoung people under 29 years old accounted for two thirds of the total populationof Saudi Arabia. The external factor is information technology development suchas the internet. The identity of metal music performers in Saudi Arabia is differentfrom the identity of metal music performers in general. Saudi Arabia metal groupidentity can be seen in Saudi Arabia Metal which is the first organization of rockand metal in Saudi Arabia.